Behavioral science in the global arena : global health trends and issues - Congress, Elaine Piller; Meister, Dalton; Osborn, Shenae; Takooshian, Harold (Emerald Publishing Limited : IAP, Information Age Publishing, Inc., 2022)
"This book focuses on global health - trends and issues. The topic of the chapters in this book are particularly relevant now that our world is struggling to survive the pandemic. At the United Nations we are very aware of the third sustainable development goal, the promotion of good health and well-being. Knowing the current crucial trends and issues impacting health around the world are crucial in realizing this goal. Thus, this book looks at health issues affecting certain populations as well as the impact of health disparities, climate change, and biodiversity in promoting good health and well-being. This third book in the UN book series continues with the three principal tenets of the UN Book Series. 1. The key current issues that affect our world are addressed. Since COVID 19 has had a devastating global impact, this book focuses on the major health issues and trends 2. As the problems facing our world are very complex, there is need for many voices from different disciples to address these challenging issues. Thus, this book includes authors from our professions of psychology and social work, as well as medical doctors, scientists, and NGO leaders. 3. This book is co-edited and co-authored by students and recent graduates. Students have much to contribute beyond technological skills and generation of literature reviews. Thus, in this book they equally share in editorship and authorship of chapters. This book is written for anyone interested in global health. It should be of particular importance for faculty, students, and practitioners who would like to learn more about current trends and issues in global health"-- Provided by publisher.
Keywords: Sustainable Development Goals.; World health.; Psychology -- Research -- International cooperation.; Psychology -- Mental Health.; Psychology.; elektronické knihy; electronic books